2010
DOI: 10.1002/hep.23528
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Virologic Response Prevents the Development of Esophageal Varices in Compensated, Child-Pugh Class A Hepatitis C Virus–Induced Cirrhosis. A 12-Year Prospective Follow-Up Study

Abstract: The incidence of de novo development of esophageal varices (EV) in patients with compensated liver cirrhosis has been determined by few studies in the short term and never in the long term. The aims of the present study were to determine the incidence and the risk factors associated with the development of EV and to assess whether antiviral treatment and achievement of sustained virologic response (SVR) may prevent de novo EV development in patients with HCV-induced cirrhosis. We studied 218 patients with comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
115
1
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(127 citation statements)
references
References 26 publications
8
115
1
3
Order By: Relevance
“…To our knowledge, no study has compared the survival rate of patients with UD ascites with that of patients with overt ascites so far. Regrettably, we did not compare a reference population of patients with compensated cirrhosis but we observed that the 3-year mortality rate of patients with UD ascites was approximately eightfold higher than the one reported by other previous investigations in patients with compensated disease ( 33,34 ). Th is fi nding, in addition to the rapid progression of overt ascites in approximately one-fi ft h of cases, is relevant from a clinical point of view and consistent with the assumption that UD ascites represents a very early stage of liver decompensation.…”
Section: Guarantorsmentioning
confidence: 59%
“…To our knowledge, no study has compared the survival rate of patients with UD ascites with that of patients with overt ascites so far. Regrettably, we did not compare a reference population of patients with compensated cirrhosis but we observed that the 3-year mortality rate of patients with UD ascites was approximately eightfold higher than the one reported by other previous investigations in patients with compensated disease ( 33,34 ). Th is fi nding, in addition to the rapid progression of overt ascites in approximately one-fi ft h of cases, is relevant from a clinical point of view and consistent with the assumption that UD ascites represents a very early stage of liver decompensation.…”
Section: Guarantorsmentioning
confidence: 59%
“…4,5 Eradication of HCV with antiviral therapy reduces the risk of hepatic decompensation, hepatocellular carcinoma, and death from a liver-related cause or any cause. [6][7][8][9][10] Among patients with HCV infection and cirrhosis in whom peginterferon-ribavirin treatment has failed, rates of sustained virologic response to retreatment with interferon-containing regimens are as low as 14%. [11][12][13][14][15][16][17][18][19] In addition, treatment for HCV infection, especially with interferoncontaining regimens, in patients with cirrhosis is associated with increased toxic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, será a mediolargo plazo cuando se puedan percibir los resultados sobre las complicaciones y la mortalidad asociada a esta enfermedad, así como su impacto sobre el consumo de recursos sanitarios. La RVS se ha asociado a una regresión de la fibrosis 27 y a una disminución de la progresión de la enfermedad en pacientes tratados con regímenes basados en interferón 28 . Del mismo modo, parece probable que el daño hepático se vea frenado en los pacientes que alcancen RVS con AAD, tendiendo el pronóstico a asimilarse al de la población nunca infectada cuando la fibrosis sea leve o moderada.…”
Section: Discussionunclassified